Therapeutic efficacy of salvage hyperbaric oxygen therapy in sudden sensorineural hearing loss after failure of steroids - İmre, Abdulkadir; Aladağ, İbrahim; Pınar, Ercan; Aslan, Hale; Duran, Rıdvan; Yazır, Mustafa (ENT Updates, 2017)
Objective: The aim of this study was to evaluate the efficacy of hyperbaric oxygen (HBO) therapy as salvage therapy in patients with idiopathic sudden sensorineural hearing loss (ISSNHL) after failure of systemic therapy. Methods: Forty-eight consecutive patients with refractory ISSNHL were enrolled retrospectively. All patients were given systemic steroid therapy by tapered doses. In addition, forty-one patients received intratympanic dexamethasone injection. Hearing outcomes were determined by recovery rate according to Siegel's criteria and hearing gains in pure-tone average (PTA) measured by audiometry before and after HBO therapy. The effects of prognostic factors on hearing recovery were also evaluated. Results: Thirteen (27%) patients responded to HBO therapy. The remaining 35 (73%) patients did not show any improvement. After HBO therapy, significant improvement was found in mean hearing thresholds at all frequencies. Only the level of initial PTA level and gender were significantly associated with recovery. Patients with severe hearing loss (≥70 dB) had significantly better results. Conclusion: Salvage HBO therapy may be beneficial in patients with ISSNHL who failed to recover by primary combined steroid therapy. Further hearing recovery with salvage HBO therapy can be expected, particularly in patients with PTA greater than 70 dB.